2018
DOI: 10.2147/ccide.s157840
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D and orthodontics: an insight review

Abstract: Vitamin D is known as the oldest of all hormones. 7-Dehydrocholesterol is converted to previtamin D3. It becomes a secosteroid when it is later converted to 1,25-dihydroxyvitamin D3 (1,25(OH)2D3). A number of factors influence vitamin D3 production, including skin pigmentation, the use of sunscreen lotions, season, latitude, and altitude. Vitamin D is important for bone metabolism and calcium hemostasis. Researchers have linked a deficiency in vitamin D levels to a number of systemic complications, including c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 58 publications
(112 reference statements)
0
9
1
2
Order By: Relevance
“…Briefly, our results do not support that physiological concentrations of 25(OH)D 3 may enhance the OTM, however it is possibly involved in the reestablishment of bony tissue supporting the teeth after OTM. Also, our results do not support that vitamin D deficiency leads to a slower rate of OTM, as proposed in a recent review [ 33 ].…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Briefly, our results do not support that physiological concentrations of 25(OH)D 3 may enhance the OTM, however it is possibly involved in the reestablishment of bony tissue supporting the teeth after OTM. Also, our results do not support that vitamin D deficiency leads to a slower rate of OTM, as proposed in a recent review [ 33 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Although the connection between vitamin D, vitamin D receptor (VDR) and orthodontic phenotypes is not a new subject in the literature and has been investigated by some dental researchers in the past three decades [ 33 ], the role of vitamin D as a therapeutical adjunct during OTM is still controversial and the molecular processes occurring during OTM under the influence of vitamin D are largely unknown. Therefore, this in vitro study aimed to investigate, if 25(OH)D 3 impacts on the expression of some genes involved in the response of hPDL fibroblasts to simulated orthodontic compressive strain.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…8 Vitamin D in orthodontics have been studied for its potential stimulation of osteoclastic activity and its role in increasing orthodontic tooth movement. 9,10 No previous studies associating vitamin D and its effect on orthodontic pain perception could be found in literature. The purpose of our study was to find if there is any association between orthodontic pain perception and serum vitamin D levels in patients undergoing orthodontic treatment.…”
Section: Introductionmentioning
confidence: 99%